“We’re one side of the wall and they’re the other”: An Interpretative Phenomenological Analysis study exploring parents’ and young people’s experiences of family engagement during the Education, Health and Care needs assessment process - Eccleston, Sally (2016)
There have been a number of significant developments in the practice of Local Authorities and schools following the publication of the Children and Families Act 2014 and the Special Educational Needs and Disability Code of Practice: 0-25 years 2015 (Department for Education (DfE) & Department of Health (DoH), 2015). Key changes include a new co-ordinated Education, Health and Care (EHC) needs assessment process, and the introduction of EHC plans to replace Statements of Special Educational Need (SEN). Notably, the views, wishes and feelings of young people and their families are increasingly viewed as being central to decision making processes at individual and strategic levels. The present research draws a link between this emphasis in legislation and the wider notion of family engagement, which concerns families, communities and schools working together to create effective partnerships. To date, whilst outcome focused research has suggested that family engagement can have a positive impact on a wide variety of academic, social and emotional outcomes for young people, there has been a distinct lack of research considering the experiences and perceptions of families regarding their engagement in educational processes. Consequently, this research takes an Interpretative Phenomenological Approach to consider in depth four parents’ and two young people’s experiences of the Education, Health and Care Needs assessment process, and specifically their experiences of family engagement within this. Semi-structured interviews were undertaken with all six participants, and following the analysis of the resultant data using Interpretative Phenomenological Analysis, seven master themes were interpreted by the researcher. Some of the main principles of the Children and Families Act 2014 were reflected in the interpreted themes: multi agency support, working in partnership with a keyworker, a child-focused approach, and aspects of family engagement, including family participation. However, contrary to legislation, the participants here found it difficult to understand the purpose of the EHC needs assessment process, and identified a distinct lack of knowledge about statutory assessment. In addition, families experienced a power hierarchy throughout the process, with professionals continuing to hold the dominant position. This was demonstrated through one family member describing how she felt that her and her family were on “one side of the wall” and professionals involved in the decision making process were on “the other”. This research therefore has significant implications for practitioners working within Local Authorities and schools regarding building positive relationships with families, and how to ensure that families truly feel empowered and are able to participate in flexible ways during the EHC needs assessment process, as recent legislative changes intend.